Tailoring Single-Mode Random Lasing of Tin Halide Perovskites Integrated in a Vertical Cavity - Adl, Hamid Pashaei (Advanced materials (Deerfield Beach, Fla.), 2024)
© 2024 The Authors. Advanced Materials published by Wiley‐VCH GmbH.